MAKSIM KERJA SAMA KUANTITAS DAN PENYIMPANGANNYA DALAM FILM JAWA WOKO CHANNEL “BONDO NEKAT” - Prihartini, Indah Dwi; Maharani, Aulia (Jurnal Online Baradha, 2024)
ABSTRACT The use of everyday language shows that language is an important part of communication, one of which is the language in the short film "Bondo Nekat" by Woko Channel. This research examines the maxim of cooperation, especially the maxim of quantity. This research is entitled "The Quantity Cooperation Maxim and Its Deviations in the Jawa Woko Channel Film "Bondo Nekat". This research attracted the attention of researchers because the speech or conversation that occurred in this film was in line with or complied with the maxim of cooperation. So it can be seen what forms of speech comply with the maxim of quantity as well as the forms of deviation from this maxim. Based on this, this research has a problem focus, namely what is the form of the maxim of quantity cooperation and its deviations in the Jawa Woko Channel film "Bondo Nekat"? From this description, the aim of this research is to explain the form of the maxim of quantity cooperation and its deviations in the Jawa Woko Channel film "Bondo Nekat". This research is descriptive qualitative in nature. Data and data sources were taken from the YouTube Woko Channel with the film Bondo Nekat. The data collection technique used is the listening and note-taking technique. Data is presented informally. The results of this research indicate that the speech in the Jawa Woko Channel film "Bondo Nekat" is in line with the maxim of quantity. Keywords: Maxim of Quantity, Deviation, Pragmatics